2018
DOI: 10.1111/imb.12377
|View full text |Cite
|
Sign up to set email alerts
|

Alimentary microbes of winter‐form Drosophila suzukii

Abstract: Drosophila suzukii (Matsumura) (Diptera: Drosophilidae) is a damaging pest of fruit. Reproductively diapausing adults overwinter in woodlands and remain active on warmer winter days. It is unknown if this adult phase of the lifecycle feeds during the winter period, and what the food source may be. This study characterized the flora in the digestive tract of D. suzukii using a metagenomics approach. Live D. suzukii were trapped in four woodlands in the south of England and their guts dissected for DNA extractio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
31
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 27 publications
(35 citation statements)
references
References 46 publications
3
31
0
1
Order By: Relevance
“…Previous studies had also shown that gut symbionts in stinkbugs (Acrosternum hilare; Hemiptera: Pentatomidae) and harlequin cabbage bug (Murgantia histrionica; Heteroptera: Pentatomidae) are significantly influenced by temperature (Prado et al, 2010). A special core gut microbiome that was identified in the spotted wing Drosophila (Drosophila suzukii, Diptera: Drosophilidae) was also associated with a cold, wet climate (Fountain et al, 2018).…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…Previous studies had also shown that gut symbionts in stinkbugs (Acrosternum hilare; Hemiptera: Pentatomidae) and harlequin cabbage bug (Murgantia histrionica; Heteroptera: Pentatomidae) are significantly influenced by temperature (Prado et al, 2010). A special core gut microbiome that was identified in the spotted wing Drosophila (Drosophila suzukii, Diptera: Drosophilidae) was also associated with a cold, wet climate (Fountain et al, 2018).…”
Section: Discussionmentioning
confidence: 97%
“…Although the tropical areas have high temperatures all year, they have two seasons of rain and drought and the highest annual temperature and precipitation. Latitude, temperature, and moisture are most important ecological factors that affect the diversity of insect gut microbiota (Kikuchi et al, 2016;Fountain et al, 2018). Previous studies had also shown that gut symbionts in stinkbugs (Acrosternum hilare; Hemiptera: Pentatomidae) and harlequin cabbage bug (Murgantia histrionica; Heteroptera: Pentatomidae) are significantly influenced by temperature (Prado et al, 2010).…”
Section: Discussionmentioning
confidence: 99%
“…While a high number of reproduction hosts is known from fruit sampling and lab studies, the complete feeding ecology is yet to be described. Early attempts to identify the ingested plant DNA and microbes in the guts of adult individuals have been successful [12,13]. Further studies using these techniques will help to understand the whole feeding ecology of this pest species.…”
Section: Introductionmentioning
confidence: 99%
“…Yet, it has. Using a metagenomics approach, Fountain et al (2018) concluded that the microbiome of wintering adults from four different woodland areas in S. E. England showed no major differences in their microbiomes. In their study there was no snow cover preventing the flies from feeding on various substrates.…”
Section: How Do the Host And Microbes Deal With Overwintering Diapausmentioning
confidence: 99%
“…The idea of gut microbiome replenishing has been challenged by Pais et al (2018) and was previously discussed. A similar study to Fountain et al (2018) needs to be done on the microbiome of the crop (i.e. the crop has been ignored in this species) in a temperate area where snow covers the ground preventing feeding.…”
Section: How Do the Host And Microbes Deal With Overwintering Diapausmentioning
confidence: 99%